The Impact of Digitalization on Strategic Management: A Bibliometric Analysis of Technology Integration in Strategic Decision Making - Loso Judijanto; Moh. Hafidurrahman; Efti Novita Sari; Suriah Hanafi (West Science Journal Economic and Entrepreneurship, 2023)
This research conducts a comprehensive bibliometric analysis to explore the impact of digitalization on strategic management, with a specific focus on the integration of technology in strategic decision-making. The analysis spans the years 2002 to 2023, incorporating peer-reviewed articles and conference papers from prominent databases such as Scopus, Web of Science, and PubMed. The study employs citation analysis, co-citation analysis, and keyword analysis to uncover influential works, thematic clusters, and prevalent research themes within the literature. Key findings reveal a steady increase in publications over the past two decades, indicative of the growing scholarly interest in the intersection of digitalization and strategic decision-making. Seminal works, including "Implanting strategic management" by Ansoff et al. and "Strategic Management: Concepts & Cases Competitiveness and Globalization" by Hitt et al., continue to wield substantial influence. Clusters identified through co-citation analysis reflect themes such as digital business, SME strategies, customer-centric approaches, and the integration of artificial intelligence. Keyword analysis underscores the prominence of terms like development, capability, and the digital economy, signifying a comprehensive exploration of the multifaceted nature of digitalization's impact on strategic decision-making. The analysis also highlights evolving research agendas, with a shift towards dynamic capabilities, digital platforms, and customer-centric strategies. This research contributes to the understanding of the current state of research in digitalization and strategic management, offering insights for scholars, practitioners, and policymakers navigating the dynamic landscape of digital transformation.